PENGARUH PERSEPSI SISWA TENTANG KOMPETENSI KEPRIBADIAN GURU TERHADAP PRESTASI BELAJAR DI SMK PANCA BHAKTI - Amalia, Rheina; Sulistyarini, Sulistyarini; Purwanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research was intended to investigate whether there was or not a significant effect of students’ perception of teacher’s personal competence on students’ learning achievement at basic accountancy subject of tenth graders of vocational school Panca Bhakti Sungai Raya. The research employs quntitative research with expost-facto design. The subject of the study was 42 students of tenth grade of accountancy department at vocational school Panca Bhakti Sungai Raya with academic year 2018/2019. The data were collected using a questionnaire which had already been validated its reliabilty and validity. The collected data then were analyzed using SPSS 18. Performing regression linear test on X and Y variable, it was found that the students’ perception of teacher’s personal competence provided a positive effect on students’ learning achievement with equality of regression Y = 77.129 + 0.426X and contributed 21% variances. Subsequently, the hypothesis testing was caried out by comparing the level of significance of the study and t-value with that 0.05 and t-table, in which it was indentified that its significance level occured at 0.00, namely less than 0.05 (p<0.05) and the t-value was 4.192 which was more than the t-table 2.021, (4.92>2.021 ). As such, it was inferred that the (Ho) was rejected and the (Ha) was accepted. In other word, there was a significant effect of students’ perception of teacher’s personal competence on students’ learning achievement at basic accountancy subject of tenth graders of vocational school Panca Bhakti Sungai Raya.Keywords: students’ perception of teacher’s personal competence, students’ learning achievement.